1991
DOI: 10.1103/physrevb.43.6598
|View full text |Cite
|
Sign up to set email alerts
|

Infrared analysis of clustering in the II-VI-VI compoundCdSexTe1

Abstract: Infrared reAectivity spectra at 82 K for Bridgman-grown CdSe Te& crystals (x =0. 05-0.35) show the two expected transverse-optical phonon modes and an unexpected third mode. Analysis of the data, using the cluster model of Verleur and Barker, shows that these spectra represent substantial nonrandom clustering of the anions around the cations. The magnitude and x dependence of the clustering is similar to that seen in the related compound CdSe, S&, grown at the same temperature, although by a different growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
4
29
0
Order By: Relevance
“…As generally reported, ternary tetrahedron coordinated A 1-x B x Z and AY y Z 1-y systems ( [12][13][14][15] for FIR and [16][17][18][19][20][21][22][23][24][25][26][27][28] for EXAFS), as well as balanced quaternaries of type A 1-x B x Y y Z 1-y (such as GaInAsSb [29] for EXAFS, CdMnSeTe [30] for EXAFS and [6,31] for FIR, analyzed in [32], ZnCdSeTe [33] for FIR), and unbalanced quaternary A 1-x-x′ B x′ C x Z (such as MnCdHgTe [34], ZnCdHgTe [35,36]), or AX y Y y′ Z 1-y-y′ system FIR spectra all exhibit SOPs; such preferences are linked to the thermodynamic properties of each system.…”
Section: Introductionsupporting
confidence: 67%
“…As generally reported, ternary tetrahedron coordinated A 1-x B x Z and AY y Z 1-y systems ( [12][13][14][15] for FIR and [16][17][18][19][20][21][22][23][24][25][26][27][28] for EXAFS), as well as balanced quaternaries of type A 1-x B x Y y Z 1-y (such as GaInAsSb [29] for EXAFS, CdMnSeTe [30] for EXAFS and [6,31] for FIR, analyzed in [32], ZnCdSeTe [33] for FIR), and unbalanced quaternary A 1-x-x′ B x′ C x Z (such as MnCdHgTe [34], ZnCdHgTe [35,36]), or AX y Y y′ Z 1-y-y′ system FIR spectra all exhibit SOPs; such preferences are linked to the thermodynamic properties of each system.…”
Section: Introductionsupporting
confidence: 67%
“…In Α1-x B x C and ΑC1-yDy ternary or A1-xBxC1-yDy quaternary compounds a basic question concerns a random or non-random substitution of the Α by B and C by D ions in respective sublattices. The first answer to this question has been obtained from infrared phonon mode analysis for GaΡl-yΑsy [1], CdS1-ySey [2], Cd1-x HgxΤe [3] and CdTe1-y Sey [4] ternary alloys. In all these experiments an additional feature in the infrared reflectivity spectrum has been observed and interpreted as a result of next nearest neighbours clustering [1][2][3][4].…”
mentioning
confidence: 99%
“…The first answer to this question has been obtained from infrared phonon mode analysis for GaΡl-yΑsy [1], CdS1-ySey [2], Cd1-x HgxΤe [3] and CdTe1-y Sey [4] ternary alloys. In all these experiments an additional feature in the infrared reflectivity spectrum has been observed and interpreted as a result of next nearest neighbours clustering [1][2][3][4]. The information concerning the partial clustering of ternary compounds have been also obtained from nuclear magnetic resonance in CdHgTe [5] and recently, in extended X-ray absorption fine stucture (EXAFS) analysis for diluted magnetic semiconduction ZnMnSe [6], as well as for non-magnetic quaternary In1-x Gax Sb1-y Asy alloys [7].…”
mentioning
confidence: 99%
“…The total number of cp-pairs Β(x) for a given k-filling is Γ Particular ion-ion interactions may or may not be negligible in preferring one site--occupation to another, i.e., the selections have, respectively, random or biased distribution. In general, let wkNsl stand for the site-occupation biasing weights In analyzing tetrahedral coordination experimental results, D(x (then a 4th power curve) is often approximated by a parabola P*(x) [2,4,5]. To satisfy normalization and conditions at the limits, P*(x) must be of the form is an arithmetic series with decrement 1/3(α -1).…”
Section: Random and Biased Site-occupation Analysismentioning
confidence: 99%
“…Site-occupation preferences (S-OP) of infrared lattice vibration spectra for tetrahedrally coordinated III-V and II-VI group ternary compounds [1,2] are confirmed by extended X-ray absorption fine structure (EXAFS) analysis in ternary ZnMnSe [3] and quaternary GaIn1-xAs y Sb1-y [4], Cd1-x Μnx Sey Τe 1 -y [ 5] a nd (497) Zn0.5 Cd0.5 Se0.5 Τe0.5 [6]. It has been shown that GaAs and In-Sb pairs are preferred to In-As and Ga-Sb pairs in GaInAsSb [4], Mn-Se and Cd-Te to Mn-Te and Cd-Se in CdMnSeTe (for x < 0.2; y < 0.2) [5], and Zn-Se and Cd-Te to Zn-Te and Cd-Se in ZnCdSeTe [6].…”
Section: Introductionmentioning
confidence: 99%